Analyzing The Serial Mediation of Customer Brand Co-Creation Behavior and Perceived Value in Enhancing Revisit Intention - Purnami, Ni Made; Mujiati, NI Wayan; Kartika Sari, Uswatun Siwi; Da Costa, Carla Alexandra De Jesus; Putri Darmadi, Desak Komang Dea Marcellina (Universitas Brawijaya, Indonesia, 2024)
The café industry faces increasing competition, particularly in attracting and retaining Generation Z customers who prioritize unique experiences and emotional connections. This study aims to examine the direct and indirect effects of place attachment, customer brand co-creation behavior, and perceived value on revisit intention among Generation Z customers in Bali. Additionally, it explores the serial mediation effects of customer brand co-creation behavior and perceived value in this relationship. Data was collected through structured questionnaires from a sample of 300 café visitors in Bali, selected using purposive random sampling. The collected data was analyzed using SmartPLS 3.0. The results indicate that place attachment has a significant direct effect on revisit intention and an indirect effect mediated by customer brand co-creation behavior and perceived value. Furthermore, the study confirms the serial mediation role of these variables, highlighting their combined influence on strengthening revisit intention. These findings underscore the critical importance of fostering emotional bonds and actively engaging customers in brand-related activities to enhance perceived value and encourage repeat visits. The results provide valuable insights for café managers aiming to build long-term loyalty among Generation Z consumers by implementing strategies that integrate emotional and experiential elements.